Clinical audit of inherited bleeding disorders in a developing country - Sajid Raihan; Khalid Safoorah; Mazari Nazish; Azhar Waleed; Khurshid Mohammad (Wolters Kluwer Medknow Publications, 2010)
Objective: We did a clinical audit to determine the status of coagulation disorders in a hemophilia care center in Pakistan. Setting: Fatimid foundation blood bank and hematological diseases center, Lahore. Study Design: This is a retrospective descriptive study. Materials and Methods: All patients registered at Lahore center were included. Data was collected using a questionnaire including age, gender, diagnosis, hepatitis and human immune deficiency virus (HIV) status, number of episodes of bleeding, most common site of bleeding, severity of disorder and number of transfusions required to treat the episode. Results: During the study period, a total of 923 registered patients were reviewed at Lahore center and of these, 408 patients (44.2%) were on regular follow-up. Inherited bleeding disorders identified in these patients included hemophilia A, hemophilia B, vWD, factor VII deficiency, factor V deficiency, factor X deficiency, dysfibrinogenemia, afibrinogenemia, factor XIII deficiency; and platelet function defects. Median age was 17 years with a range of three to 57 years. Median age at diagnosis was one year. There were 329 (80.6%) males and 79 (19.3%) females. The products used in these patients included factor VIII concentrate, fresh frozen plasma, cryoprecipitate, cryosupernatant and platelets. Testing for transmission of viral infections was also done in these patients and one patient (0.2%) was found hepatitis B positive, six patients (1.4%) were hepatitis C positive and two patients (0.49%) were HIV positive. Conclusion: Hemophilia A, hemophilia B and vWD are the commonly encountered inherited bleeding disorders in our patients followed by other recessively transmitted disorders with a median age of 17 years and male to female ratio of 4: 1. Most of the patients utilized services available at Fatimid foundation with good clinical results. In Pakistan, non-governmental organizations (NGOs) are trying their best for providing optimal treatment to patients with inherited bleeding disorders. There is a need for government participation to improve the availability of current hemophilia care services.